2022
DOI: 10.1155/2022/3733656
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of miR-124-3p Silencing on Neuronal Damage in the Hippocampus of Depression Rats by Regulating STAT3 Gene

Abstract: Objective. A large amount of evidence shows that the abnormal expression of miRNA plays an important role in the development of depression. Therefore, we investigated the effect of miR-124-3p on neuronal damage in the hippocampus of depression rats. Methods. The target genes of miR-124-3p were predicted by the database; the depression model was prepared by subcutaneous injection of corticosterone (CORT), and LV-miR-124-3p asponge lentiviral suspension was given to determine the weight of rats and open-field te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
4
1
0
Order By: Relevance
“…For instance, the expression of miR-146a was negatively correlated with the degree of depression [ 12 ]. Moreover, miR-124-3p expression was increased in the brain of the depressed patients, and similar results were obtained in the serum of depressed patients [ 13 ]. Additionally, miR-497 level was overexpressed in CUMS-induced rats [ 14 ].…”
Section: Introductionsupporting
confidence: 68%
“…For instance, the expression of miR-146a was negatively correlated with the degree of depression [ 12 ]. Moreover, miR-124-3p expression was increased in the brain of the depressed patients, and similar results were obtained in the serum of depressed patients [ 13 ]. Additionally, miR-497 level was overexpressed in CUMS-induced rats [ 14 ].…”
Section: Introductionsupporting
confidence: 68%
“…Both DICER1 and miR-124 genes were upregulated in rats with hyperthyroidism in the current study. Previous studies have reported the upregulation of miR-124 in the brains of both depressed rats and humans. , Promoting hippocampal neuronal apoptosis and reducing BDNF expression, as reported later in the current study, could offer an explanation for the detrimental impact of miR-124 in the development of mood illnesses in hyperthyroidism …”
Section: Discussionsupporting
confidence: 76%
“…Previous studies have reported the upregulation of miR- 124 in the brains of both depressed rats and humans. 27,28 Promoting hippocampal neuronal apoptosis and reducing BDNF expression, as reported later in the current study, could offer an explanation for the detrimental impact of miR-124 in the development of mood illnesses in hyperthyroidism. 28 Activation of β-catenin by thyroid hormones was reported in different cells.…”
Section: ■ Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%